1986
DOI: 10.1126/science.3484838
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptide Structure of Bursin, a Selective B-Cell-Differentiating Hormone of the Bursa of Fabricius

Abstract: Differentiation of lymphoid precursor cells in a variety of species is induced by polypeptide hormones such as thymopoietin for T cells and bursin for B cells. In the present experiments, bursin isolated from the bursa of Fabricius of chicken was found to induce the phenotypic differentiation of mammalian and avian B precursor cells but not of T precursor cells in vitro. Similarly, bursin increased cyclic guanosine monophosphate in cells of the human B-cell line Daudi but not in cells of the human T-cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Later on, a tripeptide hormone isolated from extracts of the Bursa of Fabricius and named bursopoietin or bursin, induced early B-cell differentiation (Brand et al, 1976;Audhya et al, 1991;Audhya et al, 1986).…”
Section: T Is Well Established That the Bursa Of Fabriciusmentioning
confidence: 99%
“…Later on, a tripeptide hormone isolated from extracts of the Bursa of Fabricius and named bursopoietin or bursin, induced early B-cell differentiation (Brand et al, 1976;Audhya et al, 1991;Audhya et al, 1986).…”
Section: T Is Well Established That the Bursa Of Fabriciusmentioning
confidence: 99%
“…Bursin, a tripeptide hormone of B cell differentiation (2), induced Bu-1 alloantigens and B-L antigens on the surface of precursor cells (9). The defect of differentiation of bursal stem cells in a cellimpermeable chamber suggested the significance of direct cell-to-cell contact (34).…”
mentioning
confidence: 99%
“…In particular, REC cells are addressed to participate with macrophages, dendritic cells and elements of the extracellular matrix in the formation of a bursal microenviroment for lymphoid cell maturation (Glick, 1995). During the last decade, it was suggested that bursal medullary REC might be a source of bursin (Audhya et al, 1986;Viamontes et al, 1989), a peptide which selectively induces the differentiation of committed Blymphocyte precursor cells (Audhya et al, 1986). The presence of UCN-like-ir in bursal epithelial cells suggests a role for this peptide in the bursal lymphoid cell maturation.…”
mentioning
confidence: 99%